Sypmtomatology of Tobacco Mosaic Virus (TMV) and Chilli Veinal Mottle Virus (CVMV) on six local Chilli - Sulaiman, Inon; Gim, Wee Ngo (1981)
Single and mixed inoculations of tobacco mosaic virus (TMV) and chilli veinal mottle virus (CVMV) were carried out mechanically on one month old seedlings of stx local chilli cultivars to study symptomatology. Test seedlings singly infected expressed symptoms typical of the ISolate whereas mixed infection resulted in plants showing combined symptoms of both Isolates.